2012
DOI: 10.2503/jjshs1.81.48
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Bearing Suppresses Citrus FLOWERING LOCUS T Expression in Vegetative Shoots of Satsuma Mandarin (Citrus unshiu Marc.)

Abstract: Citrus trees alternate between rich and poor crops and are known to be alternate-bearing crops. Alternate bearing results from suppression of flowering due to bearing of fruits. To understand the molecular mechanism how fruit bearing affects flowering, we investigated the relationship between fruits and a flowering-related gene, citrus FLOWERING LOCUS T (CiFT). On trees with different amounts of fruits, the fruit weight/leaf area ratio at harvest was negatively and highly correlated with CiFT expression in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…In our experiments, the accumulation of CiFT mRNA was suppressed in fruiting trees and closely related to the fruit load and number of flower buds the following spring (Table 1); these results corroborated previously reported data (Nishikawa et al, 2012). The suppression of CiFT expression by fruit bearing indicates that CiFT expression is correlated to alternate bearing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our experiments, the accumulation of CiFT mRNA was suppressed in fruiting trees and closely related to the fruit load and number of flower buds the following spring (Table 1); these results corroborated previously reported data (Nishikawa et al, 2012). The suppression of CiFT expression by fruit bearing indicates that CiFT expression is correlated to alternate bearing.…”
Section: Discussionsupporting
confidence: 92%
“…It has been indicated that citrus FLOWERING LOCUS T (CiFT) plays an important role in the flowering of citrus and that fruit bearing suppresses floral induction via the suppression of CiFT expression (Nishikawa, 2013;Nishikawa et al, 2007Nishikawa et al, , 2012. In recent years, transcriptomic and proteomic analyses have been conducted regarding alternate bearing in citrus (Muñoz-Fambuena et al, 2013a, b;Shalom et al, 2012Shalom et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit removal also promotes floral induction (GarciaLuis et al, 1986;Iwasaki, 1959;Nishikawa et al, 2012;Okuda et al, 1996). In satsuma mandarin, the presence of fruit on the tree results in a gradual inhibition of floral induction.…”
Section: ) Flowering-affecting Factorsmentioning
confidence: 99%
“…In satsuma mandarin, the presence of fruit on the tree results in a gradual inhibition of floral induction. Early thinning of fruit increases flower number in the following spring (Garcia-Luis et al, 1986;Iwasaki, 1959;Okuda et al, 1996) and the number of fruit on the tree is negatively correlated with flower number in the following year (Nishikawa et al, 2012).…”
Section: ) Flowering-affecting Factorsmentioning
confidence: 99%
See 1 more Smart Citation